The relationship between silver crucian carp (Carassius auratus gibelio bloch) and fish poulations of natural waters - Bársony, Péter; Vinginder, Csaba (Acta Agraria Debreceniensis, 2007)
The fisheries management on inland waters is very complicated. Often the unclear propriety rights make the normal management difficult, and other times the stocking of the waters is problematic. In the last hundred years a lot of new fish species have been introduced to Hungary. Lot of them have found their place in the Hungarian fishfauna, till others have caused big problems for the fish farmers, and the anglers too. The biggest problem was caused by the topmouth gudgeon (Pseudorasbora parva Schlegel, 1842) brown bullhead (Ictalurus nebulosus LeSueur, 1819) and the silver crucian carp (Carassius auratus gibelio Bloch, 1782). In this article I show what kind of problems were caused by the silver crucian carp, because it seems that this fish is the most harmful.The damage caused by silver crucian carpposesa complex question. To get into the ponds and rivers, the crucian carps occupy the territory form the native fishspeciesandthesilvercrucian carp competes with these fishes for food, too.The silver crucian carphasa special reproduction method and because of this the speciesis expand rapidly. The silver crucian carp is able to reproduce with other cyprinids, and because the female silver crucian carps are triploids every fingerlings will be silver crucian carp.This fish is a vectorfora lot of diseases, which can easily spread over for other species.